Covid-19 Self-Isolation Telemedicine Service User Satisfaction in Indonesia - Aulia Wulandari; Febrianti Febrianti (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
The Covid-19 Self-Isolation Telemedicine Service is established to reduce hospital occupancy rates amid peak Covid-19 cases. To develop better services, user satisfaction should be measured through service quality dimensions. This study aimed to determine the service quality dimensions of Indonesia's Covid-19 self-isolation telemedicine service. A cross-sectional design was utilized for this study. Out of 124,010 service users, data from a sample of 400 respondents were collected through online questionnaires. Service quality dimensions studied were responsiveness, reliability, information quality, empathy, ease of use, and perceived usefulness. Data were analyzed using the Spearman Rank correlation test. 91.7% of respondents were satisfied with the Covid-19 self-isolation telemedicine service. Responsiveness, reliability, information quality, empathy, ease of use, and perceived usefulness were correlated with user satisfaction, with the successive level of correlation (r): 0.474, 0.569, 0.485, 0.478, 0.569, and 0.478. All dimensions studied were correlated with user satisfaction at moderate and positive levels. However, few users were dissatisfied with the Covid-19 Self-Isolation Telemedicine Service. Several efforts are required to improve the service. This study provides new insights into telemedicine satisfaction in Indonesia because it analyzes the Covid-19 self-isolation telemedicine service provided by the Indonesian Ministry of Health for the first time.